2000
DOI: 10.1159/000016618
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics of <i>Streptococcus mutans</i> for Calcium and Casein Phosphopeptide

Abstract: Casein phosphopeptides (CPP) stabilize amorphous calcium phosphate (ACP) and may be used to localize ACP in dental plaque, maintaining a state of supersaturation with respect to tooth enamel, reducing demineralization and enhancing remineralization [Reynolds, J Dent Res 1997;76:1587–1595]. The aim of this paper is to investigate these effects by measuring the affinity and capacity of Streptococcus mutans for CPP–ACP. Using the equlibrium dialysis system described by Rose and Hogg [Biochim Biophys Acta 1995;124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 18 publications
6
69
2
2
Order By: Relevance
“…When CPP-ACP is added to the oral cavity, the sticky CPP part bonds readily to the biofilms and surrounding oral tissue, leaving calcium and phosphate in high concentrations at the tooth surface to effect remineralisation. 19 Studies have shown that Recaldent is effective in preventing and reversing early caries. 20 Following whitening procedures, the application of Recaldent might also provide a rapid desensitising effect through rapid protein binding deposition of calcium and phosphate ions within the exposed dentinal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…When CPP-ACP is added to the oral cavity, the sticky CPP part bonds readily to the biofilms and surrounding oral tissue, leaving calcium and phosphate in high concentrations at the tooth surface to effect remineralisation. 19 Studies have shown that Recaldent is effective in preventing and reversing early caries. 20 Following whitening procedures, the application of Recaldent might also provide a rapid desensitising effect through rapid protein binding deposition of calcium and phosphate ions within the exposed dentinal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Derived from the milk protein, casein, and digested by the enzyme trypsin, one of the most important features of CPP is their abil ity to stabilise amorphous calcium phos phate (ACP), preventing its precipitation in solution. The spectrum of action of the CPP-ACP complex is broad, buffer ing pH, preventing demineralisation and allowing for remineralisation.…”
Section: Discussionmentioning
confidence: 99%
“…CPP can help to replace the minerals that were previously lost consequently to caries [66][67]. Hence, there is a great interest in developing CPP as nutraceutical ingredients for the formulation of functional foods.…”
Section: Bioactive Peptides Released In Vitro By the Hydrolysis Of MImentioning
confidence: 99%
“…This preparation is claimed to stabilize calcium and phosphate ions in high concentrations by binding ACP to pellicle and plaque of the tooth surface. Moreover, CPP-ACP inhibited the adhesion of Streptococcus mutans to the tooth surface producing a copious reservoir of bioavailable calcium ions [67]. Cheese and yogurt CPP have the ability to stabilize calcium phosphate in solution, forming small CPP-ACP nanocomplexes.…”
Section: Anticariogenic Effect Of Cpp In Yogurt and Cheesementioning
confidence: 99%
See 1 more Smart Citation